Análise da co-contração muscular em idosos com Doença de Parkinson durante simulação de travessia de rua - Lima, Kennedy Rodrigues (2019)
Introduction: Parkinson's Disease (PD) is characterized by the presence of tremors, muscular rigidity, slow movement and postural imbalance. Postural instability is a consequence of changes caused by PD, such as the oscillation of the center of gravity and the presence of co-contraction, impairing the execution of an efficient and safe gait. Method: The study included 19 elderly patients with idiopathic PD classified in levels I and II of Hoehn and Yahr. The volunteers were submitted to the gait analysis under the following situations: 1st - Gait at preferred speed; 2nd - Gait with simulation of crossing street; 3rd - Gait with simulation of street crossing in reduced time. The evaluation of the gait was performed by the Electromyography (EMG) surface of the vastus lateralis, femoral biceps, anterior tibial and lateral gastrocnemius muscles. For the analysis of the EMG information, the total of 10 consecutive passes of each of the three gait conditions evaluated was considered. Muscle co-contraction was calculated by the agonist / antagonist ratio of the average of activation in each gait condition of the muscles studied. Result: no significant differences were found in the co-contraction of the muscles evaluated between gait conditions. Conclusion: There was no significant difference in the co-contraction of the elderly people with PD in the gait conditions evaluated, maybe because these individuals already walk in high co-contraction, and are unable to adapt to the demands of a dual functional task, such as the street crossing.